Description of Rotylenchus zhongshanensis sp. nov. (Tylenchomorpha: Hoplolaimidae) and discovery of its endosymbiont Cardinium. (20th July 2022) - Guo, F.; Castillo, P.; Li, C.; Qing, X.; Li, H.
Abstract: A new bisexual species of Rotylenchus is described and illustrated based on morphological, morphometric and molecular characterizations. Rotylenchus zhongshanensis sp. nov. is characterized by having a conoid lip region complying with the basic pattern for Hoplolaimidae, but with pharyngeal glands slightly overlapping intestine dorsally and cuticle thickened abnormally in female tail terminus. Females have robust stylet (30.1–33.8 μm). The pharyngeal gland has short dorsal (11.2–16.8 μm) overlap on the intestine. The vulva is located at 48.0–56.5% of body length, and phasmids are pore-like, 4–6 annuli posterior to the anus. For males, phasmids are pore-like, 11–17 annuli posterior to cloaca. The spicules are ventrally arcuate (21.0–28.5 μm) with gubernaculum in 5–8 μm length. The rRNA and mitochondrial COI genes were successfully sequenced from the assembled whole-genome sequences of the new species, and were used for reconstructing the phylogenetic relationships of the new species. A new strain of cyto-endosymbiont Cardinium was also discovered from the genome sequences of R. zhongshanensis sp. nov. The 16S rRNA phylogeny analyses revealed that this new bacterial strain is closed to that from cyst and root-lesion nematodes.